2021
DOI: 10.1186/s12889-021-10962-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards a needs-based design of the physical rehabilitation workforce in South Africa: trend analysis [1990–2017] and a 5-year forecasting for the most impactful health conditions based on global burden of disease estimates

Abstract: Background Rehabilitation can improve function in many people with chronic health conditions. It is important to consider priority conditions requiring rehabilitation, so it can be realistically positioned and costed in national health financing systems like South Africa (SA)‘s proposed National Health Insurance (NHI). This paper describes temporal trends of top-ranked conditions on years lived with disability (YLDs) rates in SA, for which physical rehabilitation can ameliorate associated disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…South Africa has a unique epidemiological profile and the need for rehabilitation services is substantial. 24 Although life expectancy increased between 1990 and 2017, the country is experiencing colliding epidemics of communicable and noncommunicable diseases, which have changed disease profiles and trends. In addition, people are living with increased morbidity and a poorer quality of life, both of which can be ameliorated by rehabilitation.…”
Section: Rehabilitation In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…South Africa has a unique epidemiological profile and the need for rehabilitation services is substantial. 24 Although life expectancy increased between 1990 and 2017, the country is experiencing colliding epidemics of communicable and noncommunicable diseases, which have changed disease profiles and trends. In addition, people are living with increased morbidity and a poorer quality of life, both of which can be ameliorated by rehabilitation.…”
Section: Rehabilitation In South Africamentioning
confidence: 99%
“…A 2021 analysis found that almost 60% of all years lived with disability in South Africa were due to conditions amenable to rehabilitation, including ( Fig. 1 ): 24 (i) human immunodeficiency virus infection and acquired immunodeficiency syndrome (with resultant tuberculosis); (ii) chronic respiratory disease; (iii) type 2 diabetes mellitus; (iv) low back pain and other musculoskeletal disorders; (v) age-related and other hearing loss; (vi) neonatal disorders; (vii) congenital birth defects; (viii) lower limb, upper limb, spinal and multiple fractures and dislocations; (ix) cardiovascular disease and stroke; and (x) burns.…”
Section: Rehabilitation In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…YLDs are increasing at a higher rate in low- and middle- income countries (LMICs), compared to high- income countries (HICs) [ 7 ]. In South Africa (SA), YLDs due to health conditions that contribute to most disability increased by about 270% from 1990–2017, with a further 6% predicted increase from 2017–2022 [ 8 ]. Thus, health systems in LMICs need to adapt in response to the epidemiological transitioning reflective of high levels of morbidity and functioning problems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was done by describing the most prevalence types of functioning problems (impairments, activity limitations and participation restrictions). These functioning problems were associated with the top 10 conditions contributing most to years lived with disability in South Africa and for which evidence-based rehabilitation interventions to address associated disability exist [ 8 ]. The most prevalent functioning problems were mapped to the ICF framework.…”
Section: Introductionmentioning
confidence: 99%